(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article deals with the results of the studying of the language culture of a personality as the psychological phenomenon. Functions, structurally informative and operational characteristics of this phenomenon have been described. The language culture peculiarities of junior students with speech disorders and those who are with normal speech development are investigated. The relation between the components of language culture formation and academic achievement in language subjects have been revealed. The data can be used by educators and psychologists to predict aptitude to low language culture.